2015
DOI: 10.1590/s0102-865020150110000009
|View full text |Cite
|
Sign up to set email alerts
|

Rutin ameliorates methotrexate induced hepatic injury in rats

Abstract: Rutin may be a potential adjuvant drug to reduce the hepatic side effects observed during Mtx therapy for various clinical conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 22 publications
5
36
0
Order By: Relevance
“…RUT, like many flavonoids, has demonstrated antioxidant properties [52], in addition to the ability to relieve oxidative stress in biological systems. We observed that RUT exhibited antioxidant effects against intestinal mucositis, increasing GSH levels and decreasing MDA levels in mice presenting 5-FU-induced intestinal mucositis; this was consistent with the findings of previous studies that demonstrated that RUT exerts antioxidant effects by decreasing MDA levels [53,54] and increasing GSH and superoxide dismutase levels [55][56][57].…”
Section: Discussionsupporting
confidence: 92%
“…RUT, like many flavonoids, has demonstrated antioxidant properties [52], in addition to the ability to relieve oxidative stress in biological systems. We observed that RUT exhibited antioxidant effects against intestinal mucositis, increasing GSH levels and decreasing MDA levels in mice presenting 5-FU-induced intestinal mucositis; this was consistent with the findings of previous studies that demonstrated that RUT exerts antioxidant effects by decreasing MDA levels [53,54] and increasing GSH and superoxide dismutase levels [55][56][57].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, rutin always provided significant improvement regarding liver injury in the results, which suggested that it can be regarded as the functional compound of red quinoa bran. In the previous study, rutin also has been proven the protective effect on methotrexate-induced liver injury in rats [19].…”
Section: Discussionmentioning
confidence: 99%
“…Rubin (2001) postulated that severe degeneration of cell organelles especially the mitochondria and the rough endoplasmic reticulum, could be attributed to the oxygen metabolites with deficiency of the protective enzymes from the liver following drug treatments. Erdogan et al (2015) suggested that Mtx increased MDA levels which confirmed the oxidative stress and explained the tissue damage.…”
Section: Discussionmentioning
confidence: 85%
“…The mechanisms of Mtx toxicity are not yet fully understood, but recent studies have shown that a decrease in the levels of cellular glutathione (GSH) and oxygen radicals are linked with the development of Mtx-induced toxicity ( Johovic et al, 2003 ;Cetinkaya et al, 2006;Sener et al, 2006 ;Cetin et al, 2008;Erdogan et al, 2015).It was demonstrated that cytosolic nicotinamide adenosine diphosphate (NADP)-dependent dehydrogenases are inhibited by Mtx, suggesting that the drug decreases the availability of NADPH in cells. Under normal conditions, NADPH is used by glutathione reductase to maintain the reduced state of GSH, an important cytosolic antioxidant that protects cells against reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%